(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The COVID-19 pandemic crisis in 2020 had a significant influence on women entrepreneurs’ commercial activity. Changes in the scope, style, and structure of business in most small or medium firms, including those owned or managed by women, have been impacted by pandemic protection measures implemented to limit health hazards or the adoption of new restrictions. The goal of the study was to obtain insight into the impacts of the pandemic on women’s companies as well as balancing business or family duties of women entrepreneurs in the altered conditions since prior research had shown that women bore the brunt of the crisis. The study was carried out using an online survey with a total of 93 participants (women entrepreneurs in Delhi). The findings revealed that the COVID 19 pandemic harmed 78 percent of women-owned businesses and that women compensated for the loss of hours spent at work by working at home and caring for family members. Owning a company may provide women with the independence they want as well as the economic and social success they need. On a national level, business ownership is crucial for future economic progress.